2019
DOI: 10.1002/admi.201900963
|View full text |Cite
|
Sign up to set email alerts
|

A Thermodynamic Description of Turbulence as a Source of Stochastic Kinetic Energy for 3D Self‐Assembly

Abstract: The extent to which one can use a thermodynamic description of turbulent flow as a source of stochastic kinetic energy for 3D self‐assembly of magnetically interacting macroscopic particles is investigated. It is confirmed that the speed of the objects in the flow field generated in this system obeys the Maxwell–Boltzmann distribution, and their random walk can be defined by a diffusion coefficient following from the Einstein relation. However, it is discovered that the analogy with Brownian dynamics breaks do… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 60 publications
(118 reference statements)
0
9
0
Order By: Relevance
“…The experimental setup was introduced and characterized in (24,25). New to this setup was a cone-shaped inset, which created a flow gradient meant to center particles in the middle and prevent interaction with the top and bottom.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental setup was introduced and characterized in (24,25). New to this setup was a cone-shaped inset, which created a flow gradient meant to center particles in the middle and prevent interaction with the top and bottom.…”
Section: Methodsmentioning
confidence: 99%
“…The adjustable turbulence in the flow created disturbing forces to enable the system to reach the global energy minimum. These disturbing forces provide stochastic kinetic energy to the objects, leading to a motion analogous to Brownian motion (25).…”
Section: Introductionmentioning
confidence: 99%
“…Moving to even larger scales, the contribution from Löthman et al pertains to an intriguing class of works that aim to investigate whether macroscopic systems can be used to reproduce the phenomenology of microscopic or molecular systems or, conversely, the extent to which the thermodynamic description of the latter can be used to capture self‐assembly in systems where gravity and inertia are to be reckoned with [ 24 ] – for the same reason that makes them observable without microscopes, i.e., size. [ 25 ] The authors present a study on a macroscopic fluidic system where spherical magnetic particles are suspended and interact thanks to a turbulent flow field. Having previously showed that their system can reproduce the Maxwell‐Boltzmann statistics of particle motion in dilute gases, [ 26 ] here Löthman et al analyse the functional analogy between temperature and turbulence as source of particle mobility respectively at molecular and macroscopic scale.…”
Section: Figurementioning
confidence: 99%
“…mechanical vibration, heat, external field. 12,[16][17][18][19][20][21][22][23][24][25][26][27] Kinetic traps are intermediate states with local energy minima that hinder the evolution towards the most stable target configuration. 28,29 Reversible bonds may help to overcome kinetic traps and correct errors during assembly.…”
Section: Introductionmentioning
confidence: 99%